Is Delaying Cord Clamping until Placenta Delivery Beneficial? Oxygen Saturation and Heart Rate Transition during the Initial 5 Minutes after Delivery in Indian Healthy Newborns - Mukherjee, Suchandra; Bulsara, Jignesh S.; Das, Manoja Kumar; Waratakar, Yogendra; Saha, Anindya Kumar; Dubey, Sunil; Mehta, Pratima; Gupta, Bini; Singh, Arun K.; for Indian Delayed Cord Clamp Study Group (American Journal of Perinatology, 2020)
Objective This study aimed to compare the preductal oxygen saturation (SpO2) and heart rate (HR) in newborns during the initial 5 minutes after birth with delayed cord clamping (DCC) and early cord clamping (ECC) practices at sea level.Study Design This prospective observational study included newborns born at >34 weeks vaginally (Dharampur, Gujarat) or through caesarean section (CS) (Kolkata, West Bengal). In Dharampur, the newborns received ECC practice (8 weeks) followed by DCC practice (10 weeks). In Kolkata, the newborns received ECC practice only (8 weeks).Results The newborns with DCC (n = 170) had significantly higher SpO2 (3–8%) throughout than those with ECC born either vaginally (n = 178) or through CS (n = 101). The newborns with DCC had slower rise in HR during the first 2 minutes than those with ECC. The 5th and 10th percentile values of SpO2 for newborns with DCC practice were higher than those with ECC practice.Conclusion The trends of SpO2 and HR during the first 5 minutes after birth indicate a relatively smoother cardiopulmonary transition by delaying cord clamping till placental delivery compared with early clamping. The reference ranges can be used for Indian newborns born by uncomplicated vaginal delivery with DCC during the first 5 minutes.
Keywords: cord clamping; early; delay; oxygen saturation; hear rate; percentile; sea level